Evaluation of the Effectiveness of Mobile Phone Built-in Cameras for the 3D Documentation of Archaeological Sites - الخليل عمر; علي أحمد; حمدان أمجد (Latakia University Journal -Engineering Sciences Series, 2022)
Cultural heritage all over the world, especially in Syria, is in danger of being destroyed due to some natural (earthquakes, weather and climate conditions) or human activities (wars, poor preservation and maintenance). Therefore, an effective method must be used to document and preserve this heritage. 3D models of archaeological sites are considered one of the most important inputs to the documentation process. The current study evaluates the effectiveness of images taken by a set of mobile phone built-in cameras for 3D modeling of the archaeological site known as the Panorama of the Sheikh Khalil Al-Khatib (Tartous). To evaluate the resulted 3D, it was compared with a 3D model of the same site generated from images taken by a professional camera. Experience has proven that the geometric accuracy of the resulting models ranges between (8-17) mm, and it can provide detailed measurements suitable for documentation proces.